Monte Carlo simulations of the switching processes in the superconducting quantron-based neuron. Issue 1 (January 2021) - Gorchavkina, A A; Bastrakova, M V; Klenov, N V; Satanin, A M
Abstract: We study the response function of a superconducting single-contact interferometer (quantron or rf-SQUID), which is the building block for adiabatic neuron with a nonlinear transfer characteristic. It is shown that the intrinsic shunt capacitance of the junction leads to distortions in the response function. At the same time the contact resistance leads to the suppression of these vibrations. The response function of the rf-SQUID at finite temperature is calculated by Monte Carlo method.